Effect Of Nano-Zno On Growth Of Mung Bean (Vigna Radiata) And Chickpea (Cicer Arietinum) Seedlings Using Plant Agar Method (Applied Biological Research, 2011)
The present study demonstrates the effect of nano-ZnO particles on growth  of mung bean (Vigna radiata) and chickpea (Cicer arietinum) seedlings. The  study was conducted in plant agar media to prevent precipitation of water insoluble nanoparticles in test units. Various concentrations of nano-ZnO  particles in suspension form were introduced to the agar media and its effect  on root and shoot growth of seedlings examined. Analytical techniques like optical microscopy and scanning electron microscopy were used to study the  architecture of root. Inductive coupled plasma (ICP) was used to determine  the uptake of nano-ZnO particles by root. The best response of nano-ZnO on  mung bean was observed at 20 ppm and on chickpea at 1 ppm, beyond these  concentrations the seedling showed retardation in growth and de
Keywords: Biomass; chickpea; Cicer arietinum; mung bean; nano-ZnO; toxicity; Vigna radiata